Study Influence of Nursing Home Care upon Complications of Immobility in Musculoskeletal System in Patient with Stroke that Admitted at Home in the City of Semnan 1381- 82 - Mohammad Ali Hosseini; Hamid Reza Khankeh; Sefollah A'laei; Maral Dibaei (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: In the world, stroke causes long-term complication and is considered an the important cause in these inability in patients. Therefore, nursing care is very important in this patient that must determine reachable and supportive goals. We can decrease the problems in these patients, their families and treatment-care system with implementation good program. Materials & Methods: This investigation is a semi-experimental study which its main goal has been to determine the effect of home care on complication resulting from immobility in musculoskeletal system of patients with stroke stayed at home. Association of investigation all the patients with stroke stayed at home which have been hospitalized at one of the hospitals of Semnan town in winter of 1381 and summer of 1382, among them 32 persons were chosen accidentally (16 person test group and 16 person witness group). Collection of data was instrument includes a questionnaire consisting of two parts. The first part demographic characteristic of patients with stroke and the second part as checklist which mentioned questions is in musculoskeletal system which completed by the researcher. After selection of samples and completion of questionnaire and graphic and checklist at the begining of the work, for patients of test group, nursing cares have been varried out by emphasising and focusing on musculoskeletal system for 12-18 session, each session 45 minutes to one hour (total 40 days) and for witness group no special care has given (But they were free in receiving care and if anyone had used this care, he/she expelled from samples). Results: Research demographic profile indicated that 23 persons of samples are man (13 persons in test group and 10 persons in witness group) and 8 persons are woman (3 person in test group and 5 person in witness group). Mean of age is 63 in test group and 70 in withness group. Mean of weight is 67/5 kg in test group and 65 kg in witness group. In comparing immobility complication between two groups in muscloskeletal system (0.06) there were meaningful statical difference. Conclusion: Obtained finding in relation to the major goal of the investigation showd that the amount of complication resulting from immobility in test group, according to assumption has been lower than persons who don't receive these cares, Nursing care was considered to be more effective on complication resulted from immobility of patients with stroke.